2023
DOI: 10.3126/jbpkihs.v6i1.53763
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescribing Pattern among the Inpatients in the Surgery Department of Tertiary Hospital of Eastern Nepal

Abstract: Background: Prescription is a written instruction by a health care personnel to pharmacist to dispense drug(s). Irrational drug prescribing is a global problem, particularly in developing and transitional countries. This study was conducted to see the status of World Health Organization (WHO) core prescription indicators, complementary indices and prescription errors. Methods: It was a quantitative cross-sectional descriptive study carried out among inpatients of general surgery of tertiary hospital in eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Compared to the standardized range of 13.4-24.1%, our hospital seems to follow moderate trends. It is worth noting that other studies have observed even higher injection use [14,15] however the fact that the usage of injectables which fell within the recommended range in certain studies cannot be negated [16,17]. Excessive injection use can in ate costs and increase risks of mortality and morbidity, as highlighted by the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the standardized range of 13.4-24.1%, our hospital seems to follow moderate trends. It is worth noting that other studies have observed even higher injection use [14,15] however the fact that the usage of injectables which fell within the recommended range in certain studies cannot be negated [16,17]. Excessive injection use can in ate costs and increase risks of mortality and morbidity, as highlighted by the WHO.…”
Section: Discussionmentioning
confidence: 99%